Two siblings with late infantile form of Metachromatic leukodystrophy – a case report: Prikaz primera dveh sorojencev s pozno infantilno obliko metakromatske levkodistrofije - Vogrin, Bernarda (Acta Medico-Biotechnica, 2025)
Metachromatic leukodystrophy is an autosomal recessive neurodegenerative disease. The underlying mechanism of disease is the lack of arylsulphatase A, which leads to the accumulation of sulphated glycosphingolipids. Three forms of disease are recognized based on clinical onset, including infantile, juvenile, and adult forms. Until recently, metachromatic leukodystrophy was untreatable. In this article, we present the cases of a sister and brother with the late infantile form. The female was diagnosed when the disease was at an advanced stage, and thus, was treated palliatively. Her younger brother was diagnosed at the pre-symptomatic stage and experimental genetic treatment was conducted, which markedly Improved the course of disease.